Answers

2014-11-04T17:42:19+05:30
we know
sin(90-Ф)=cosФ
so...
sin20=cos70
so,
=sin20×cos70+cos20×sin70
=sin²20+cos²20
by pythagoras identity,
sin²+cos²=1
so
sin20×cos70+cos20×sin70=1

0
sin(X + Y) = sinX cosY + cosX sinY
so sin 20 x cos 70 + cos 20 x sin 70 = sin(20+70) = sin 90 = 1
2014-11-04T18:00:58+05:30
Sin20*cos70+cos20*sin70            (let this be eq. 1)
cos(90-Ф)=sinФ
and
sin(90-Ф)=cosФ
substituting these in eq. 1,
sin20*cos(90-20)+cos20*sin(90-20)
=sin20*sin20+cos20*cos20
=sin²20+cos²20
taking 20=Ф
the eq. is
sin²Ф+cos²Ф
this is equal to 1
therefore answer is equal to 1

0